A) -2,8 * (-1) * (-1,1)=
b) -1,1 * (-11,1) * (-1,11)
c)-2 * (-4,4) * (-1) * (-3,3)
d)-2 1/3 * (-0,6) * 2 2/5 * (-1 1/9)
e)-3 3/4 * (-3 3/5) * (-0,625) * (-1,4)
f)-2 2/3 * (-1,5) * (-3 1/3 ) * (-0,6) * (-1)
g)- 8/3 * (-3,14) * (-1 5/7) * (-1) * [-(-14)]

a)-12 2/3 : 3 1/6 =
b) 4 1/6 : (-1 2/3)=
c)-6,3 :(-2,1)=
d)-6,8 :(-1,7)
e)-9,2 : (-0,05)=
f)-4,03:5=
g) 6,72: (-0,6)

ale zeby nie były same wyniki

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-18T20:22:54+01:00
A) 4,9
b) -13,31
c) -10,7
d)
e) 695/100
f)2,9
g)

a) 22
b) 308
c) -8,4
d) -8,5
e) -9,25
f) -0,806
g) 6,12